2019
DOI: 10.1111/hae.13868
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise in people with haemophilia: An umbrella review of systematic reviews and meta‐analyses

Abstract: Haemophilia is a genetic X-linked congenital haemorrhagic disorder characterized by a deficiency in the production of coagulation factors VIII and IX corresponding to haemophilia types A and B, respectively. 1,2 Although rare, with a frequency of 1 in 10 000 births, haemophilia can be found in about 400 000 people worldwide. 3 Approximately 85% of haemorrhagic episodes occur in the musculoskeletal system, hemarthroses and intramuscular haematomas, resulting in the main complications of haemophilia: pain, muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 48 publications
1
27
0
1
Order By: Relevance
“…Poor-quality studies and lack of reporting of methods and findings mean that care must still be taken with such recommendations. 28,29 However, as shown in our findings, safety in participation with gymbased exercise programs was demonstrated. It is noteworthy that none of the studies included in these two reviews used private gym facilities -they were either home exercise programs or physiotherapy rehabilitation facilities.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Poor-quality studies and lack of reporting of methods and findings mean that care must still be taken with such recommendations. 28,29 However, as shown in our findings, safety in participation with gymbased exercise programs was demonstrated. It is noteworthy that none of the studies included in these two reviews used private gym facilities -they were either home exercise programs or physiotherapy rehabilitation facilities.…”
Section: Discussionsupporting
confidence: 66%
“…Recent reviews of exercise for people with hemophilia have been broadly encouraging with regard to its safety as an intervention. Poor‐quality studies and lack of reporting of methods and findings mean that care must still be taken with such recommendations 28,29 . However, as shown in our findings, safety in participation with gym‐based exercise programs was demonstrated.…”
Section: Discussionmentioning
confidence: 71%
“…Los autores solo incluyeron RS (independientemente del metaanálisis). También en Brasil, Siqueira et al (23) describieron la calidad de la evidencia sobre el efecto del ejercicio físico en pacientes con hemofilia. Los autores incluyeron 10 RS.…”
Section: Ejemplos De Autores Latinoamericanosunclassified
“…PT programmes based on therapeutic exercise have been proven to be useful treatments contributing to the development of aerobic capacity, flexibility and strength, and improving the health status of the musculoskeletal system of PWH, without adverse effects 10 . Despite some studies have shown the positive effect of PT and patient education in improving the perception of pain of PWH, 11 research about pain management strategies included in PT interventions is scarce.…”
Section: Introductionmentioning
confidence: 99%